KAJIAN STRATEGI NELAYAN UNTUK MEMPERTAHANKAN HIDUP DI TANJUNG KRAMAT KOTA GORONTALO PROVINSI GORONTALO - Erlyna Wida R (Universitas Sebelas Maret, 2005)
The potential of Tominigulf is a gift from God but in other side that became hard problem. This problem and neglected of fisherman community, risk and uncertainty fish cacthed especially famine season. The aim of this research to know various strategy that used by fisherman to survive his life in Tnajung Kramat, so it could be expected gave recommendation to improve fisherman prosperity. The necessary strategy to develop are business diversification, make use of loan to productive business, and efficiency cost of head seaward